2004
DOI: 10.1023/b:jonb.0000017867.70191.68
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Emotions in the Hand Movement Quality of Finnish Sign Language

Abstract: This study investigated whether people can decode emotion (happiness, neutrality, and anger) communicated via hand movements in Finnish sign language when these emotions are expressed in semantically neutral sentences. Twenty volunteer participants without any knowledge of sign language took part in the experiment. The results indicated that the subjects were able to reliably decode anger and neutrality from the quality of hand movements. For happy hand expressions, the responses of happiness and neutrality we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…It remains to be investigated whether specific hand movement forms are relevant cues for emotion expression. However, few studies on emotional prosody in sign language suggest that emotion can be conveyed via hand movement qualities such as shape and position in space (Hietanen et al 2004;Reilly et al 1992). …”
Section: Methodological Benefits Of the Bap For Emotion Researchmentioning
confidence: 99%
“…It remains to be investigated whether specific hand movement forms are relevant cues for emotion expression. However, few studies on emotional prosody in sign language suggest that emotion can be conveyed via hand movement qualities such as shape and position in space (Hietanen et al 2004;Reilly et al 1992). …”
Section: Methodological Benefits Of the Bap For Emotion Researchmentioning
confidence: 99%
“…Qualities were mentioned as an important diagnostic aspect of psycho-pathological disorders in the psychiatric literature [19]. For example, the movement behaviour of schizophrenic patients is usually described as "angular, jerky, and uncoordinated, with uneven acceleration and deceleration and as either too slow or too fast a tempo" [10]. Psycho-pathological disturbances are associated to "disturbed, abrupt, halted, and stilted" gestures.…”
Section: Definitionsmentioning
confidence: 99%
“…It is also found that the perception of finger motion can change the interpretation of the entire displayed scene. In another study [45], it is reported that the underlying emotions conveyed during Finnish sign language communication were recognized by those having no knowledge of the language itself. Furthermore, neuroscientists report engagement of different perceptual and visuomotor processes when observing actions demonstrated on virtual hand-like structures as compared to real hand movements [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%